2012
DOI: 10.1172/jci61852
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector integration in the human genome induces alternative splicing and generates aberrant transcripts

Abstract: Retroviral vectors integrate in genes and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 33 publications
(59 reference statements)
3
135
0
3
Order By: Relevance
“…Through highly sensitive yet very specific techniques, these chimeric ("read-through") transcripts were systematically detected in populations of transduced cells. While neither study could claim a strong quantitative power, the examination by Mavilio and colleagues of a limited set of integrants revealed read-through transcripts for more than half of the targeted genes in all cell types tested (13).…”
Section: Nature's Insolent Unpredictabilitymentioning
confidence: 96%
See 3 more Smart Citations
“…Through highly sensitive yet very specific techniques, these chimeric ("read-through") transcripts were systematically detected in populations of transduced cells. While neither study could claim a strong quantitative power, the examination by Mavilio and colleagues of a limited set of integrants revealed read-through transcripts for more than half of the targeted genes in all cell types tested (13).…”
Section: Nature's Insolent Unpredictabilitymentioning
confidence: 96%
“…However, in about 10% of cases, read-through mRNAs matched their physiological counterparts in abundance (13), which, considering that retroviral integration is monoallelic, suggests complete subversion of transcripts produced by the targeted locus.…”
Section: Nature's Insolent Unpredictabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…A study in mice harboring a truncated form of HMGA2 showed that overexpression of the transcript could result in benign hematopoietic stem/progenitor cell expansion (Ikeda et al, 2011). Following these observations, several groups have now shown that the generation of aberrant transcripts could indeed alter the cellular transcriptome, potentially leading to haplo insufficiency of a tumor suppressor gene (Cesana et al, 2012;Heckl et al, 2012;Moiani et al, 2012). The clinical significance of these mutagenic events, however, remains uncertain.…”
Section: Insertional Activation Inactivation and Clonal Dominancementioning
confidence: 99%